2006
DOI: 10.1002/mabi.200500225
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy and MALDI‐TOF MS Characterisation of End‐Functionalised PVP Oligomers Prepared with Different Esters as Chain Transfer Agents

Abstract: Ester-functionalised poly(1-vinylpyrrolidin-2-one) (PVP) oligomers obtained by radical polymerisation in methyl propionate, diethyl malonate and diethyl 2-methylmalonate were characterised by NMR spectroscopy, and MALDI-TOF mass spectrometry. The chain-transfer constants were determined as 5.54 x 10(-4), 1.22 x 10(-3) and 1.70 x 10(-2), respectively, by measuring the variation of the number-average molecular weight on conversion. These values were compared with those of methyl isobutyrate (1.65 x 10(-3)) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…30 The grafting degree, that is, the average number of PVP side chains per PLGA main chain of PLGA-g-PVP MP samples (calculated from the number average molecular weight of the PLGA main chain, the number average of the PVP pendants and the PLGA/PVP w/w ratio) were 1.5, 1.1, and 1.0. The grafting degree was proportional to the [T]/[M] ratio, therefore decreased by increasing the NVP content in the feed.…”
Section: /5 3 10mentioning
confidence: 99%
See 1 more Smart Citation
“…30 The grafting degree, that is, the average number of PVP side chains per PLGA main chain of PLGA-g-PVP MP samples (calculated from the number average molecular weight of the PLGA main chain, the number average of the PVP pendants and the PLGA/PVP w/w ratio) were 1.5, 1.1, and 1.0. The grafting degree was proportional to the [T]/[M] ratio, therefore decreased by increasing the NVP content in the feed.…”
Section: /5 3 10mentioning
confidence: 99%
“…The chain transfer involved one hydrogen atom a to the ester function. [23][24][25][26][27][28][29][30] Compared with ATRP or RAFT, this synthetic method gave end-functionalized oligomers with broader molecular weight distribution, but had the merit of being very simple and easily scaled-up.…”
mentioning
confidence: 99%
“…[189] [190] PVP kann durch freie radikalische Polymerisation von Vinylpyrrolidon sowie durch kontrollierte radikalische Polymerisation hergestellt werden. [174] Die zweite Methode ermöglicht niedrige PDI-Werte unterhalb von 1.2, [182,[191][192][193] variable Endgruppen [182,194] [195] Das erfolgreichste Konjugat, ein 28-kDa-PHPMADoxorubicin-Copolymer (8.5 Gew.-%; Doxorubicin PK1; klinische Studie Nr. FCE 28068 Phase III; Schema 4), wurde für mehrere Krebsarten getestet (Tabelle 3) und zeigte dabei Wirkung bei NSCLC, kolorektalen Tumoren und Mammakarzinomen.…”
Section: Poly(vinylpyrrolidon)unclassified
“…Nitrogen atom of PNVP can easily form coordinate bonds with lots of drugs, especially protein and polypeptides, which can be used as carrier of drugs. Recently, Ranucci et al (17)(18)(19)(20)reported the synthesis of hydroxyl-terminated PNVP oligmers via free radical polymerization in isopropyl alcohol (IPA), using cumene hydroperoxide as the initiator.…”
Section: Introductionmentioning
confidence: 99%